Social responsibility of higher education institutions and sustainable development - Juljana Laze (Izzivi Prihodnosti, 2024)
Research Question (RQ): This paper focuses on: a) What are the main challenges and barriers universities face when attempting to fulfil their social responsibility, and b) What innovative approaches or best practices can be identified to overcome these obstacles and enhance their social impact? b) How do universities measure and report on their social responsibility initiatives, and what are the key indicators and metrics used to assess the effectiveness and impact of these programs? c) What are the key dimensions and components of social responsibility for universities, and how do they vary across different cultural and institutional contexts?